Mental Health Screening and Consultation in Primary Care: The Role of Child Age and Parental Concerns - Godoy, Leandra (2014)
OBJECTIVE: To determine (a) how child age relates to parent concerns about child behavior and (b) how child age and parent concerns correlate with provider referrals and family attendance at mental health consultant (MHC) appointments. METHODS: Data were obtained from Rhode Island’s Project LAUNCH (Linking Actions for Unmet Needs in Children’s Health) in which universal developmental and behavioral screening and MHCs were embedded within primary care sites serving low-income, diverse families. Children 9 months to 8 years were eligible for the study if they had a scheduled screening well child visit in 2010 (N = 1,451). Families completing screening and/or those referred for a MHC appointment were included in analyses (n = 700). Outcome measures included parent reported concerns about child behavior, referral status following screening, and family attendance at the MHC appointment. RESULTS: For every 1-month increase in child age, there was a 1.02 times increase in the likelihood of parent behavioral concern and a 1.04 times increase in the likelihood of mental health referral, even when controlling for child behavior. MHC-referred children over 5 years were 2.61 times more likely to attend than children less than 5. When examining parent behavioral concerns and child age jointly, only concerns remained significant. CONCLUSION: Infants and toddlers, who have the highest rates of unmet mental health needs, may be least likely to benefit from universal screening and on-site MHC support. Efforts to incorporate behaviorally-based screening tools and increase parent concerns where appropriate appear warranted, particularly for families with very young children.